Complex optimization based on decomposition of power system modes - Tulkin Sh. Gayibov; Alisher E. Shanazarov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2025)
Relevance: the problem of complex optimization of electric power systems (EPS) modes, in general, involves determining, in each time interval of a short-term period of operation, the optimal values ​​of all controlled parameters, i.e. active and reactive powers of stations participating in optimization, reactive powers of other controlled sources, optimal voltages of reference nodes, which ensure minimum total costs associated with the generation, transmission and distribution of electricity. Solving such a problem with sufficient accuracy, taking into account the influencing and limiting conditions, requires appropriate improvement of existing mathematical models and calculation algorithms based on modern methods. The goal: it consists of improving the mathematical models of problems of complex optimization of electric power systems modes for all regulated parameters based on modern methods and developing effective algorithms for their solution when planning their short-term modes. Methods: The study uses modern theories of calculation and optimization of steady-state modes of electric power systems, methods of nonlinear mathematical programming and systems analysis.. Results: the existing models and methods of complex optimization of short-term modes of electric power systems based on decomposition are improved. The results of the study of its effectiveness are presented using the example of an 8-node test scheme of the EPS.